2021
DOI: 10.3390/ijerph18094699
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge and Practices during the COVID-19 Outbreak in the Middle East: A Cross-Sectional Study

Abstract: Objectives: This study aimed to assess the knowledge and practices of the general public in the Middle Eastern countries during the COVID-19 pandemic. Methods: A cross-sectional study using an online survey was conducted between the 19th of March and the 6th of April 2020 in three Middle Eastern countries (Jordan, Saudi Arabia, and Kuwait) to explore the knowledge and practices of the Middle Eastern population regarding COVID-19. A previously developed questionnaire was adapted and used for this study. Multipl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 17 publications
(21 reference statements)
5
33
1
Order By: Relevance
“…According to Pakistani researchers, the motivations for wearing face masks are “attitude, social norms, risk perceptions of the pandemic, and perceived benefits of face masks are the major influencing factors positively affect public willingness to wear face masks, whereas the cost of face masks and unavailability of face masks tend to have opposite effects” [ 14 ]. Compliance with preventive measures by the population, and the wearing of masks in particular, is also influenced by factors such as the region of residence (rural or urban area), housing conditions, sector of employment and education level, age, and income level [ 9 , 15 , 16 , 17 ]. American scientists have identified a high risk of COVID-19 infection for all segments of the population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Pakistani researchers, the motivations for wearing face masks are “attitude, social norms, risk perceptions of the pandemic, and perceived benefits of face masks are the major influencing factors positively affect public willingness to wear face masks, whereas the cost of face masks and unavailability of face masks tend to have opposite effects” [ 14 ]. Compliance with preventive measures by the population, and the wearing of masks in particular, is also influenced by factors such as the region of residence (rural or urban area), housing conditions, sector of employment and education level, age, and income level [ 9 , 15 , 16 , 17 ]. American scientists have identified a high risk of COVID-19 infection for all segments of the population.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to prevent the spread of rumors, myths, and misinformation regarding the current pandemic, especially among people with low socioeconomic status, because such dissemination can have serious consequences for public health [ 19 ]. Some authors recommend paying special attention to information campaigns on COVID-19 aimed at young people—in particular, university students [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 A study from three countries in the Middle East found good knowledge toward disease prevention and control and a lower knowledge score toward disease transmission. 39 Postgraduate education may help to create best practices for maximizing pharmacists' effectiveness in future emergencies. 40 In Saudi Arabia, Alahdal et al suggested that despite moderate public awareness, the general population's attitude and practice turned out to be better.…”
mentioning
confidence: 99%
“…The present study revealed that being married represents a higher probability of having a low level of knowledge. Authors such as Naser et al, 25 and Rani et al, 26 have shown associations between marital status and low levels of knowledge of COVID-19 in health professionals in Saudi Arabia, where low levels of knowledge were found in single health professionals, as opposed to married health professionals, which can be explained by cultural aspects of Eastern countries such as believing that children and young adults are at a lower risk of contracting the disease, attending crowded places such as markets and mosques, in addition to their low acceptance of the use of masks. 25,26 These results are different from what we found in our study, where a low level of knowledge in married health professional was shown, which can be explained by the fact that the proportion of single population was low (12.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Authors such as Naser et al, 25 and Rani et al, 26 have shown associations between marital status and low levels of knowledge of COVID-19 in health professionals in Saudi Arabia, where low levels of knowledge were found in single health professionals, as opposed to married health professionals, which can be explained by cultural aspects of Eastern countries such as believing that children and young adults are at a lower risk of contracting the disease, attending crowded places such as markets and mosques, in addition to their low acceptance of the use of masks. 25,26 These results are different from what we found in our study, where a low level of knowledge in married health professional was shown, which can be explained by the fact that the proportion of single population was low (12.6%). In addition, regarding the methodological aspects of the present study, one factor that may affect the results is the low participation of single people under 40 to the study, which corresponds to the age at which continuous or post-graduate training processes are carried out.…”
Section: Discussionmentioning
confidence: 99%